Detached carbonate blocks in the northern Dang area Lesser Himalaya (Nepal) - Dhital, M. R. (Journal of Nepal Geological Society, 1991)
The process of movement of roof thrust in the northern Dang Lesser Himalaya gave rise to the deformation of various incompetent beds of limestone and dolomite from the underlying Gwar Group. Some of them are also disrupted from the footwall ramp and produced a stacked imbricate antiform of carbonates. In this process the floor thrust of the duplex became more active and later the displacement continued along the same. Afterwards, another larger duplex has formed beneath the stacked antiform. As a result, underneath the roof thrust consisting of the low-grade metamorphic rocks of the Sharda Group are found the detached and haphazardly distributed carbonates from the underlying Gwar Group. Characteristic feature and mode of occurrence of the detached carbonates, their lithology, and possible mechanism of thrusting are discussed here.